Genetic enhancement of sorghum and millet residues fed to ruminants: An ex ante assessment of returns to research - Kristjanson, Patricia M.; Zerbini, E.; Rao, K.P.C.; Kiresur, V.; Hofs, P. (International Livestock Research Institute, 1999)
This ex ante impact assessment measures the potential economic impact of and returns to investment in a proposed collaborative ILRI-ICRISAT-NARS (International Livestock Research Institute-International Crops Research Institute for the Semi-Arid Tropics-national agricultural research systems) project on genetic improvement of dual-purpose (i.e. grain and fodder) sorghum and pearl millet in India. The approach taken links three methodologies to measure how much impact, where, and how to value it. A feed simulation model is used to measure the potential productivity gains from more, higher-quality crop residues in terms of meat and milk output. Primary survey data and geographic information systems (GIS) analyses of secondary data are used to assess where these gains are likely to be made. An economic surplus model that links the results of the GIS analysis with the output from the feed model is used to value the potential benefits versus the costs of the research. One hundred and four Districts of India were identified (using GIS) as the recommendation domain (RD) or zone targeted for likely adoption of improved dual-purpose genotypes. Breeders and animal nutritionists estimate that this research could potentially lead to increases in digestibility of sorghum and millet-residues ranging from 1 % to 15 %. The estimated returns to this research are attractive, even when the scope of the benefits is limited to milk and meat production in buffalo and cattle in India.